TYPE OF CYP450 2C19 GENE METABOLIZERS IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION IN THE REPUBLIC OF NORTH MACEDONIA -A PILOT STUDY - Savevska, Tamara; Efinska Mladenovska, Olivija; Stamatovska, Kristina; Otljanska, Magdalena; Arnaudova, Frosina; Otljanski, Matej; Kirijas, Meri; Brnjarchenska Blazhevska, Teodora; Sibinovska, Olgica; Milanovski, Gorjan; Iljoska, Stefani; Dobrevski, Boban; et al. (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Clopidogrel has an antiplatelet effect, which is used to reduce the risk of myocardial infarction and stroke in high-risk patients in the context of primary prophylaxis. In the body it is subjected to metabolism by the liver enzyme system CYP450. In this project, laboratory conditions have been established to determine the polymorphisms of the CYP450 2C19 gene. The structure of the polymorphisms in the CYP450 2C19 gene and the type of metabolizer has been determined.This study included 42 heart patients with St. post PCI, mean age 65-9.7 years, treated with 75 mg Clopidogrel daily. The following polymorphisms were examined: c.681G> A; c.636G> A; c.1A> G; c.1297C> T; c.395G> A; c.819 + 2T> A; c.358T> C; c.-806C> T. Appropriate laboratory conditions have been established for the precise determination of polymorphisms in the CYP450 2C19 gene and the determination of the type of metabolizer. The results showed that in our patients the largest number of polymorphisms occur at the position c.681G> A which leads to the creation of an intermediate metabolizer, while the polymorphism at the position c.-806C> T leads to the creation of an ultrafast metabolite. The largest number of polymorphisms occurs in c.681G> A CYP450 2C19 gene, which leads to the creation of an intermediate metabolizer. Because of this, and before starting the therapy in patients St. post PCI, it is necessary to first determine what clopidogrel metabolizers they are and whether they possess LF or GF alleles. Key words : clopidogrel, metabolite, polymorphisms, CYP450 2C19 gene.